Compulsory vaccination against COVID-19 in Peru, democratic legitimacy and limitation of fundamental rights - Huamán Ordóñez, L. Alberto (Derecho Público Iberoamericano, 2022)
Democratic legitimacy in the constitutional State is based on electoral processes, to endorse the exercise of power as well as to support the limitation of fundamental rights, as an extreme exercise of the space between authority and freedom, always present in today’s societies. From philosophy, as well as from political theory and constitutionalism, such ownership is granted to Parliament with all peace. However, considering the complexity of the legislative work and the need for public authorities to act in pursuit of citizens, it is currently assumed that the Executive, as head of the administration, can limit fundamental rights, which is validated by constitutional jurisprudence who understands that this is part of the technical competences in its capacity as public power...